The Use Of Android-Based Digital Game “Climbing Castle” To Enhance Grammar Mastery In Junior High School Students At JAYABAYA Learning Center Nganjuk - Sutanti, Nita; Ulum, Bahrul; Farinawati, Yeni (Amaluna: Jurnal Pengabdian Masyarakat, 2024)
Grammar is an important sub-skill that underlies other English language skills, however, learning grammar is still challenging for students. Many students have experienced difficulties in learning grammar because the learning media and methods are still lacking in increasing student learning motivation. To overcome this problem, this research aims to find out the implementation of the Android-based game “Climbing Castle” in improving the mastery of grammar. To develop students' grammar mastery skills, “Educational Game; Play while learning using Climbing Castle” was conducted at JAYABAYA Tutoring. Having a lecture, discussion, and practice methods while playing using the Climbing Castle application. The lecture method is useful for increasing motivation verbally as well as conveying the material that will be used in Climbing Castle. The practice methods are carried out to find out how much the use of the game affects student motivation. Providing playing while learning using the Climbing Castle educational game can increase student motivation in learning Grammar. The participants of this activity are JAYABAYA tutoring students consisting of 10 students who will take part in the socialization of learning utilization using the game “Climbing Castle”.